PROSEDUR PELAYANAN PERIZINAN APOTEK OLEH DINAS KESEHATAN KOTA PEKANBARU - Irsyad "; Ernawati " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2020)
In pharmacy licensing, the Health Service which is authorized by the government is required to conduct supervision and guidance to the existence of pharmacies in the city of Pekanbaru. Regulation of the Minister of Health of the Republic of Indonesia number 7 of 2017 has set operational standards for the operation of pharmacies aimed at improving optimal health services. In pharmacy facilities, pharmacy entrepreneurs are required to have a permit known as a Pharmacy License (SIA). SIA is a permit issued by the Minister to Pharmacists in collaboration with the owner of the facility to organize a Pharmacy in a particular place. However, if the SIA has not been issued by the Department of Health, the owner of the pharmacy facility can still run the pharmacy using the Pharmacy Examination Report (BAP). At present there are 256 pharmacies that have Pharmacy Licenses spread across Pekanbaru City. Despite the large number of pharmacies scattered in Pekanbaru, apparently there are still pharmacies whose establishment is not in accordance with the procedures and permit requirements and even found pharmacies that do not have a permit. The method used in this research is a qualitative method with a case study approach. Data collection is done by interview, observation and documentation. The results showed that first, the pharmacy licensing service procedure by the Pekanbaru City Health Service was not running optimally because there were still pharmacy facility owners who complained about the length of time the SIA was issued, then in terms of licensing services at the Health Service there were still inadequate pharmacy employees in terms of pharmacy licensing. Second, the factors that hinder the process of pharmacy violation in Pekanbaru City are the quality of services from the Health Service that is not optimal like human resource competency and lack of field labor. Keyword: Licensing Service Procedure, Pharmacy Licensing Requirements